Deficiency of the CYLD Impairs Fear Memory of Mice and Disrupts Neuronal Activity and Synaptic Transmission in the Basolateral Amygdala - Li, Hui-dong; Li, Dan-ni; Yang, Li; Long, Cheng (Frontiers in Cellular Neuroscience, 2021)
Fear learning and memory are crucial for animal survival. Abnormal fear memory is a hallmark of many neuropsychiatric disorders. Appropriate neuronal activation and excitability in the basolateral amygdala (BLA) are necessary for the formation of fear memory. The gene cylindromatosis (Cyld), which encodes a lysine-63 deubiquitinase, is expressed in several brain regions including the amygdala. The functions of the cylindromatosis protein (CYLD) in neuronal activity and neural circuits, and the role of CYLD in the regulation of fear memory, remain largely unknown, however. Here we report that Cyld knockout impairs amygdala-dependent tone-cued fear memory. The number of c-Fos+ neurons responding to the tone-cued fear test was reduced in the BLA of Cyld-/- mice, suggesting that the absence of CYLD causes aberrant neuronal activation. We found that this aberrant neuronal activation in the BLA of Cyld-/- mice may relate to the decreased excitability of principal neurons. Another possiblity of aberrant neuronal activation could be the impaired excitatory synaptic transmission in the BLA of Cyld-/- mice. Specifically, both the frequency of spontaneous excitatory postsynaptic currents and the amplitude of miniature excitatory postsynaptic currents in BLA principal neurons were decreased. In addition, Cyld mutation caused an increase in both the frequency of miniature inhibitory postsynaptic currents in principal neurons and the number of parvalbumin+ interneurons, consistent with excessive local circuit inhibition in the BLA of Cyld-/- mice. Taken together, these results suggest that CYLD deficiency disrupts the neuronal activity and synaptic transmission in the BLA of mice which may contribute to the impaired fear memory observed in Cyld-/- mice.